2019
DOI: 10.1002/aenm.201901687
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic MXene Textures with Enhanced Light‐to‐Heat Conversion for Solar Steam Generation and Wearable Thermal Management

Abstract: 2D materials are of particular interest in light‐to‐heat conversion, yet challenges remain in developing a facile method to suppress their light reflection. Herein, inspired by the black scales of Bitis rhinoceros, a generalized approach via sequential thermal actuations to construct biomimetic 2D‐material nanocoatings, including Ti3C2Tx MXene, reduced graphene oxide (rGO), and molybdenum disulfide (MoS2) is designed. The hierarchical MXene nanocoatings result in broadband light absorption (up to 93.2%), theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
191
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(191 citation statements)
references
References 65 publications
0
191
0
Order By: Relevance
“…Zhu and co‐workers fabricated a novel nanoporous aluminum membrane as shown in Figure 5d, and after decorating it with self‐assembled plasmonic aluminum nanoparticles, this low‐cost all Al structure was found to absorb 96% of a broad solar spectrum. [ 43 ] In a recent report by Li et al, [ 107 ] this effect demonstrated in a MXene‐based hierarchical crumbling structure (93.2% light absorption) was theoretically validated by simulated electric field distributions (Figure 5e).…”
Section: Design Principles To Approach 100% Efficiencymentioning
confidence: 52%
“…Zhu and co‐workers fabricated a novel nanoporous aluminum membrane as shown in Figure 5d, and after decorating it with self‐assembled plasmonic aluminum nanoparticles, this low‐cost all Al structure was found to absorb 96% of a broad solar spectrum. [ 43 ] In a recent report by Li et al, [ 107 ] this effect demonstrated in a MXene‐based hierarchical crumbling structure (93.2% light absorption) was theoretically validated by simulated electric field distributions (Figure 5e).…”
Section: Design Principles To Approach 100% Efficiencymentioning
confidence: 52%
“…The bioinspired MXene nanocoatings are incorporated into solar steam‐generation devices and stretchable solar/electric dual‐heaters due to its efficient light‐to‐heat conversion. Additionally, the mechanically deformed MXene structures enable the fabrication of stretchable and wearable heaters dual‐powered by sunlight and electricity, which are reversibly stretched and heated above 100 °C (Figure d) …”
Section: Electrochemical Energy Conversion and Storage Applicationsmentioning
confidence: 99%
“…[ 11 ] The hierarchical biomimetic 2D nanocoating constructed by Ti 3 C 2 T x MXene, reduced graphene oxide, and MoS 2 achieved a broadband light absorption of 93.2% and improved the performance in light‐to‐heat conversion. [ 12 ] A vertically aligned Janus MXene aerogel and 3D MXene/melamine/polyethylene foam were also designed to obtain a high efficiency of 87% and 88.7%, respectively. [ 13 ] Although numerous strategies of MXene‐based materials have been implemented to enhance the solar steam generation efficiency, there are still some issues to be considered and resolved.…”
Section: Introductionmentioning
confidence: 99%